The Economic Factors of the âAbbasid Decline During the Buwayhid Rule in the Fourth/Tenth Century - Tholib, Udjang (Al-Jamiah: Journal of Islamic Studies, 2009)
Abbasid caliphate in the fourth/tenth century suffered from a sharp economic decline. This was the result of several factors, mainly civil wars, the Zanj and Qarmatian revolts, political interference by the Turkish and Daylamite soldiers, military iqtaâ and the activity of the âayyarun. The civil wars had a destructive effect on the city of Baghdad and its citizens, ruined most of the land and caused a devaluation of dirham and dinars. The revolts of the Zanj and Qarmatians paralyzed trade in southern Iraq leading to a stagnation of currency and the banking system and a decrease in financial activity. The involvement of the Turkish and Daylamite soldiers in politics, and rivalries among them to gain power, led to the devastation of canals, dams and consequently ruined the agricultural sector. In addition, the introduction of military iqtaâ during this period resulted in the damage of cultivated lands due to their excessive exploitation and abandonment of their irrigation system. Finally, the activities of the âayyarun in looting merchants goods, burning many houses, and killing people, inflicted considerable loss on the merchants, encouraging the latter to leave Baghdad and do business in other cities.